Formulasi Sediaan Gel-Cream Minyak Atsiri Kayu Manis (Cinnamomum burmannii) Dengan Stearyl Alcohol Sebagai Emulsifier Dan Cmc-Na Sebagai Co-Emulsifier Serta Uji Aktivitas Antibakteri Terhadap Staphylococcus epidermidis - Rizky Wisnuwardani, Aldwin, Dr. TN Saifullah Sulaiman, M.Si., Apt, Rima Munawaroh, M.Sc., Apt (2017)
Cinnamon essential oils (Cinnamomum burmannii) are containing sinamaldehide and eugenol which function as an antibacterial. Cinnamon essential oils formulated into dosage forms gel-cream so as easier to apply. The purpose of this study to determine comparison of stearyl alcohol and CMC-Na concentration on the physical properties, physical stability, and gel-cream antibacterial activity against Staphylococcus epidermidis. Cinnamon essential oils taken by water vapor distillation method. Physical properties test of gel-cream consisted of pH, viscosity, spread ability, adhesiveness, physical stability with freeze thaw cycling and antibacterial with diffusion method. Antibacterial activity could be seen from the resulting inhibition zone againts Staphylococcus epidermidis. The comparison of stearyl alcohol and CMC-Na concentration used are 0,7%:0,3% (F1), 0,6%:0,4% (F2), 0,5%:0,5% (F3), 0,4%:0,6% (F4), dan 0,3%:0,7% (F5). The influence off it against to physical properties of the gel-cream can be determined by using data analysis tools ANOVA statistical test. Physical stability of gel-cream seen from the results of multivariate analysis and to determine the effect of the freeze thaw cycling antibacterial activity used paired t-test. The result showed that higher concentration of stearyl alcohol in formula can increase the viscosity so far speard ability and prolong the adhesiveness and the higher concentration of CMC-Na in formula can decrease the viscosity thus increasing the spread ability and accelerate the adhesiveness. Physical stability of gel-cream cinnamon essential oil showed that F2, F4, and F5 did not change significantly until cycle 2 of freeze thaw cycling method. Antibacterial activity of gel-cream preparation of cinnamon essential oil at F2, F3, F4, and F5 decrease the diameter of inhibitory zone after the freeze tthaw cycling.